The study of adsorption capacity of cobalt nitrtae hexahydrate onto shredded palm oil empty fruit bunches - Othman, Nur Ain Athirah (2017)
Three different concentration of cobalt nitrate hexahydrate were prepared to be impregnated onto Shredded Palm Oil Empty Fruit Bunches (SPOEFB); 1%, 3% and 5%. This process was performed in order to study the adsorption capacity of cobalt nitrate hexahydrate. The adsorption capacity increased as the cobalt nitrate hexahydrate solution increased however, a little slow down when at highest concentration (5%). The SPOEFB were treated by two ways; washed by water taps and unwashed to examine their effect on the adsorption capacity. Between that two ways, the washed SPOEFB shows the better adsorption capacity which are 0.252, 2.807 and 3.169 for 1%, 3% and 5% respectively compared to the adsorption capacity of unwashed SPOEFB which are 0.168, 2.781 and 3.144 for 1%, 3% and 5% respectively. The washed SPOEFB shows a bit higher presence of the cobalt nitrate on it compared to the unwashed SPOEFB since the washed SPOEFB had more surface area for the cobalt to be attached as the impurities on them before were more likely had been removed during the washing process.